2010
DOI: 10.1155/2010/404982
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Concha Bullosa and Nasal Septal Deviation and Their Relationship to Maxillary Sinusitis by Volumetric Tomography

Abstract: The objective of this study was to determine the prevalence of concha bullosa and nasal septal deviation and their potential relationships to maxillary sinusitis. 883 CT scans taken at Creighton University School of Dentistry from 2005 to 2008 were retrospectively reviewed for the presence of concha bullosa, nasal septal deviation, and maxillary sinusitis. 67.5% of patients exhibited pneumatization of at least one concha, 19.4% of patients had a deviated septum, and 50.0% had mucosal thickening consistent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
83
11
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 3 publications
7
83
11
5
Order By: Relevance
“…Perez et al reported it to be 80%. It was as low as 19.4% according to Smith et al (4) as they followed the strict criteria of deviation > 4mm. DNS causing a reduction in osteomeatal unit's critical area, impairing mucociliary activity and drainage is supposed to predispose to sinusitis.…”
Section: Discussionmentioning
confidence: 95%
“…Perez et al reported it to be 80%. It was as low as 19.4% according to Smith et al (4) as they followed the strict criteria of deviation > 4mm. DNS causing a reduction in osteomeatal unit's critical area, impairing mucociliary activity and drainage is supposed to predispose to sinusitis.…”
Section: Discussionmentioning
confidence: 95%
“…Concha bullosa, paradoxical concha, bifid concha, and NSD are common anatomical variants occurring in as much as 30%-70% of the population (15,23). The middle turbinate is important in the drainage of the maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…The middle turbinate is important in the drainage of the maxillary sinus. Extreme NSD can obstruct the osteomeatal unit, while the role of a minimally or moderately abnormal middle turbinate and NSD in the etiology of paranasal inflammation is controversial (23,24). These variations cause narrowing or obstruction of the osteomeatal unit, thereby reducing the normal airflow and mucociliary clearance of the sinuses.…”
Section: Discussionmentioning
confidence: 99%
“…This anatomic variation was divided into three groups according to extent of the pneumatization: lamellar type (pneumatization in the lamellar portion), bulbous type (pneumatization in the bulbous portion; Figure 5), and extensive type (pneumatization in the both vertical lamellar and inferior bulbous portion) [35]. The prevalence of the CB varies from 4.6 to 89.5% [17,[20][21][22][36][37][38][39]. This may be due to the different definition criteria for CB.…”
Section: Concha Bullosamentioning
confidence: 99%
“…It is still debated in the literature whether CB has a role in sinusitis aetiology. However, in most of the studies, no statistical significant relationship is found between the CB and maxillary sinusitis [17,[20][21][22][36][37][38][39]. Pneumatization of the superior and inferior turbinate is also called superior and inferior concha bullosa.…”
Section: Concha Bullosamentioning
confidence: 99%